Identifying postnatal depression: comparison of a self-reported depression item with Edinburgh Postnatal Depression Scale scores at three months postpartum - Fellmeth, G; Opondo, C; Henderson, J; Redshaw, M; McNeill, J; Lynn, F; Alderdice, F (Elsevier, 2019)
BACKGROUND: Early identification of postnatal depression is important in order to minimize adverse outcomes. The Edinburgh Postnatal Depression Scale (EPDS) is commonly used as a screening tool but a single, direct question on depression may offer an alternative means of identifying women in need of support. This study examines the agreement between these methods and characteristics of women who self-identify as depressed and those with EPDS ≥ 13. METHODS: Secondary analysis of two national maternity surveys conducted in England and Northern Ireland. Agreement between the direct question and EPDS scores was assessed using Cohen's kappa. Logistic regression was used to identify characteristics of women in each group. RESULTS: 6752 women were included. At three months postpartum, 6.1% of women self-identified as having depression, 9.1% scored EPDS ≥ 13, 2.8% were positive on both. Agreement between the two methods was minimal (Cohen's kappa < 0.3). Women who self-identified as having depression had higher odds of being aged > 40 years (OR 1.8; 95% CI 1.2-2.8). EPDS ≥ 13 was associated with < 16 years of education (OR 1.4; 95% CI 1.1-1.8), minority ethnicity (OR 1.4; 95% CI 1.1-1.9), living without a partner (OR 1.7; 95% CI 1.3-2.2), and a less than happy reaction to the pregnancy (OR 1.7; 95% CI 1.4-2.1). LIMITATIONS: Low survey response limits the representativeness of findings. The absence of a diagnostic interview limits conclusions on accuracy or internal validity of the measures. CONCLUSIONS:A direct question about postnatal depression may offer a valuable addition to screening tools to identify women in need of support.